Can applying renewable energy for Australian sugarcane irrigation reduce energy cost and environmental impacts? A case study approach. (10th December 2019) - Powell, Janine W.; Welsh, Jon M.; Pannell, David; Kingwell, Ross
Abstract: In Australian sugarcane production, 90% of irrigation pumps are connected to the national electricity grid. In regional Queensland, where irrigated sugarcane is grown, both the retailer and distribution network service providers are government owned and highly regulated. This study investigates options for on-farm embedded generation from a range of commercially available components, to reduce energy costs of furrow, centre pivot, and Big Gun® irrigation. This study confirms that demand-side management crucially affects the economic feasibility of embedded generation. Connection rules, such as feed-in tariffs and export limits affecting renewable embedded generation can also influence emissions abatement costs and investment returns. When export limits are allowed on larger sites (solar PV systems >40 kW), abatement costs fall from $109/t CO2 e to $18/t CO2 e and the present value of the investment improves substantially. The analysis reveals economically feasible opportunities exist for small-scale solar PV system installations (under 40 kW), reducing NPC of pumping from 12 to 25% and emission reductions ranging from 1245 t CO2 e to 1314 t CO2 e per installation over 25 years. Where a site is not eligible for a feed-in tariff, high renewable energy utilisation rates are required to make the site feasible. Batteries did not feature as an optimal component, even when battery storage and replacement values were discounted by 60%, indicating that seasonal load profiles under-use a battery investment. Therefore, batteries are inefficient and can be avoided in an irrigation microgrid. Highlights: Connection policies create an economic disincentive for renewable installations rated over 30 kW. Load-shifting energy demand to periods of renewable generation improves economic outcomes. Results are relatively inelastic to battery storage prices for irrigation pumps with a seasonal load; and. The marginal cost of abatement under the Renewable Energy Target is reduced when excess renewable energy can be exported.